The Inhibitory Effect of some Plant Extracts on some Pathogenic Bacteria - Yasmeen I. Al-Hadidy; Sabraa S. Yaseen; Ghazwan M. Saleh (Tikrit Journal of Pure Science)
The purpose of the present study is to assay the inhibitory effect of five concentrations 10, 20, 30, 40 and 50 % of the aqueous and alcoholic extracts for leaves of the Sidr (Zizyphusspin-csit) and Eucalyptus leaves (Eucalyptus camaldulensis) in vitro, against the three types of the experimental bacteria, which Escherichia coli, Staphylococcus aureus and Salmonella typhimurium for their clinical importance as common, pathogenic in urinary tract infection by using the well diffusion assay method .The results showed that antimicrobial activity depends on kind of extract and tested microorganism. and the most bioactivity was done by methanol extract than the aqueous extract, the methanolic extract of Sidr leaves presented  the inhibitory effectiveness of all the species used  in this study ,the highest inhibition was 36 mm at 50%concentration against E. coli and methanolic extract of eucalyptus leaves showed an inhibitory effect on the growth of all bacteria except E. coli, showed resistance to the extract, As for the aquatic extracts, all the bacteria species illustrated resistance to the aquatic extracts of the leaves of the Sidr except Staph .aureus Inhibition rates were recorded at 17 and 15 mm at the concentration (30 and 20%), respectively, and the aquatic extracts of Eucalyptus leaves had no inhibitory effect on the growth of all the species used in this study, except S. typhimurium bacteria and all concentrations used. The  result of the qualitative chemical detection of the active compounds found in the extract indicated that it s contains, mainly like flavonids, alkaloids, Tannins and phenols, Saponins, Glycosides. in aquatic and alcoholic extraction.